240-GHz Reflectometer-Based Dielectric Sensor With Integrated Transducers in a 130-nm SiGe BiCMOS Technology - Defu Wang, Mohamed Hussein Eissa, Klaus Schmalz, Thomas Kämpfe, Dietmar Kissinger (IEEE Transactions on Microwave Theory and Techniques, 2020)
This article presents a reflectometer-based on-chip dielectric sensor with integrated transducers at 240 GHz. The chip simplifies the measurement of a vector network analyzer (VNA) to sense the incident and reflected waves by using two heterodyne mixer-based receivers with a dielectric sensing element. Radio frequency (RF) and local oscillator (LO) submillimeter waves are generated by two frequency multiplier chains, respectively. Two back-to-back identical differential side-coupled directive couplers are proposed to separate the incident and reflected signals and couple them to mixers. Both transmission line and coplanar stripline transducers are proposed and integrated with reflectometer to investigate the sensitivity of dielectric sensors. The latter leads to a larger power variation of the reflectometer by providing more sufficient operating bands for the magnitude and phase slope of S11 . The readout of the transducers upon exposure to liquids is performed by the measurement of their reflected signals using two external excitation sources. The experimental dielectric sensing is demonstrated by using binary methanol–ethanol mixture placed on the proposed on-chip dielectric sensor in the assembled printed circuit board. It enables a maximum 8 dB of the power difference between the incident and reflected channels on the measurement of liquid solvents. Both chips occupy an area of 4.03 mm 2 and consume 560 mW. Along with a wide operational frequency range from 200 to 240 GHz, this simplified one-port-VNA-based on-chip device makes it feasible for the use of handle product and suitable for the submillimeter-wave dielectric spectroscopy applications.